Relationship between plasma asprosin, dry matter intake, and plasma glucose at different stages of lactation - Chen, Yinyin; Jiang, Maocheng; Li, Yan; Su, Yanjing; Luo, Siwei; Wu, Peng; Zhao, Guoqi; Lin, Miao; Zhan, Kang (Frontiers in Veterinary Science, 2025)
In postpartum dairy cows, dry matter intake (DMI) decreases dramatically, resulting in reduced glucose production and negative energy balance (NEB). Asprosin is a centrally acting orexigenic protein hormone secreted by adipose tissue, and it promotes glucose production in the liver. However, the effects of asprosin on hepatic glucose output in primary bovine hepatocytes, as well as the relationship between plasma asprosin and dry matter intake at different stages of lactation, have not yet been reported. Our results demonstrated that fibrillin 1 (FBN1) exhibited significantly higher mRNA expression in the mammary gland and adipose tissue. The bovine His-asprosin proteins were > 90% pure, as confirmed by Coomassie Blue-stained SDS-PAGE gel analysis. Asprosin increased (p = 0.031) the mRNA expression of phosphoenolpyruvate carboxykinase 2 (PCK2) in primary bovine hepatocytes compared to the control group. Remarkably, glucose output (p = 0.03) in the primary bovine hepatocytes exposed to asprosin was higher than that in the control group. In addition, asprosin was found to promote PKA activity in primary bovine hepatocytes. The postpartum dairy cows exhibited significantly lower plasma asprosin levels compared to those at 110 and 230 days relative to parturition (p < 0.01). Notably, plasma asprosin levels were positively correlated with DMI at different stages of lactation. These findings indicate that increased levels of circulating asprosin should be considered a novel resolution strategy for improving DMI and addressing negative nutrient balance during the postpartum period.